Accelerated varietal turnover for open-pollinated crops ( beans, sorghum, groundnuts) in Tanzania – seed sector stakeholders’ landscaping. Baseline Report - Ochieng, Justus; Birachi, Eliud Abucheli; Kessy, Radegunda; Rubyogo, Jean Claude; Odhiambo, Wilfred; Masimane, Jo; Mbugua, Mercy; Kitoto, Victor O.; Sperling, Louise; Mutua, Mercy; Kasubiri, Fadhili; Kalemera, Sylvia; et al. (2023)
The Accelerated Varietal Adoption and Turnover for Open-Pollinated Varieties (ACCELERATE) project in Tanzania aims at understanding the requirements and constraints of large and small/marketplace traders to catalyze the uptake of new varieties and how best to enable the needed partnerships across the formal, semi-formal, and informal seed sectors to accelerate varietal adoption and turnover. This is based on the demand-pull approach, in which seed largely comes from grain traders, who currently not only buy grain from small-scale producers but also supply the largest amount of planting material (seeds). Humanitarian agencies and non-government organizations (NGOs) equally create or catalyze this demand pull since they spend considerable resources on sourcing and distributing seeds to demanding and stressed areas.